Indoor Positioning System for Retail (International Journal of Engineering and Computer Science, 2015)
An indoor positioning system (IPS) is a network of devices used to wirelessly locate objects or people inside a building. With the proliferation of consumers using smart phones and tablets, enabling indoor positioning systems has become easier now with multiple enabling technologies. Today, retail purchases are happening across multiple channels like online, in-store, and mobile with the customer interaction at various touch points. But when a consumer makes a purchase in-store, i.e. in the retailers’ brick and mortar store, the shoppers’ behavior is not getting captured by the retailer. IPS is a key enabler for capturing in-store behavior of shoppers. IGATE has created an omnichannel retail solution, with IPS being one of the key technology enablers. The solution enables retailers to link shoppers’ behavior across digital and physical channels and provide shoppers with personalized promotional offers / messages during their entire shopping journey. This paper describes the high level architecture for an IPS based solutions, using retail solution as an example. The challenges and limitations in implementing the entire IPS solution, starting from the hardware installation to mobile app integration, are also detailed.